Indonesia's Economic Growth: Keynes Theory's Perspective - Tika Okviyanti; Nur Kabib (Ilomata International Journal of Social Science, 2023)
This study aims to determine the effect of inflation, Human Development Index, and ZIS on Economic Growth in Indonesia with the Consumer Confidence Index (CCI) as a moderation variable in 2011-2022. This study uses secondary data types and quantitative research types using Moderated Regression Analysis (MRA) as a data analysis technique using an analysis tool, namely Eviews version 10. Data obtained from BPS, BAZNAS, and Bank Indonesia. Sampling is using the purposive sampling method so that in this study 18 provinces were obtained as samples so that 216 research objects were obtained. The results showed that inflation has a significant positive effect on economic growth in Indonesia, the Human Development Index has a significant negative effect on economic growth in Indonesia, ZIS has no effect on economic growth in Indonesia. After a moderation test, the Consumer Confidence Index (CCI) is able to moderate and weaken the effect of inflation on economic growth, the Consumer Confidence Index (CCI) is able to moderate and strengthen the influence of the Human Development Index on economic growth and the Consumer Confidence Index (CCI) is unable to moderate the influence of ZIS on economic growth in Indonesia.